A short note on extreme sex ratio in solitary bees Osmia cornuta in semi-field trials testing the impact of neonicotinoids. Issue 3 (27th May 2019) - Strobl, Verena; Albrecht, Matthias; Radford, Sarah; Wolf, Sarah; Neumann, Peter
Abstract : The widespread prophylactic use of neonicotinoids has severe negative effects on non-target organisms that provide ecosystem services. Chronic neonicotinoid exposure led to a male-biased offspring sex ratio in the solitary bee species Osmia bicornis in laboratory experiments, but semi-field or field data are largely lacking. Here, we used semi-field experiments to investigate the potential impact of the neonicotinoid clothianidin on the sex ratio of the closely related species Osmia cornuta . Male and female individuals of O. cornuta were held in flight cages with fully blooming winter oilseed rape, treated or not with clothianidin. After hibernation, sex ratio of emerging offspring and overwintering mortality was determined. A total of 191 male and 4 female, and 203 male and 2 female O. cornuta emerged in the control and the clothianidin treatment, respectively, thereby clearly showing an extremely male-biased sex ratio. However, there was no significant clothianidin treatment effect. As sex ratio was strongly biased in both, the clothianidin and the control treatment, our data can obviously not explain the underlying mechanism. Such extreme sex ratios require more attention in semi-field studies assessing the impacts of pesticides and other stressors on solitary bees.